Staff Development and Commitment in Nigerian Colleges of Education: A Pathway to Institutional Success - Khadijatu Adanu (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2024)
Staff development and commitment are crucial to the success of Nigerian Colleges of Education. This paper explores the impact of personnel management practices, such as recruitment, training, motivation, and discipline, on staff commitment and overall institutional success. It highlights the challenges faced by Colleges of Education in the North-East region, including inadequate funding, inconsistent training, and ineffective staff motivation practices. By focusing on improving staff development and fostering a committed workforce, educational institutions can enhance productivity and achieve their educational goals. The findings suggest that systematic and planned staff development, coupled with strong personnel management practices, are essential for promoting academic staff commitment and ensuring long-term institutional success.